Characterization of the Liriodendron Chinense MYB Gene Family and Its Role in Abiotic Stress Response - Wu, Weihuang; Zhu, Sheng; Zhu, Liming; Wang, Dandan; Liu, Yang; Liu, Siqin; Zhang, Jiaji; Hao, Zhaodong; Lu, Ye; Cheng, Tielong; Shi, Jisen; Chen, Jinhui (Frontiers in Plant Science, 2021)
Liriodendron chinense (Lchi) is a Magnoliaceae plant, which is a basic angiosperm left behind by the Pleistocene and mainly distributed in the south of the Yangtze River. Liriodendron hybrids has good wood properties and is widely used in furniture and in other fields. It is not clear if they can adapt to different environmental conditions, such as drought and high and low temperatures, and the molecular mechanisms for this adaptation are unknown. Among plant transcription factors (TFs), the MYB gene family is one of the largest and is often involved in stress or adversity response signaling, growth, and development. Therefore, studying the role of MYBTFs in regulating abiotic stress signaling, growth, and development in Lchi is helpful to promote afforestation in different environments. In our research, a genome-wide analysis of the LchiMYB gene family was performed, including the phylogenetic relationship tree, gene exon-intron structure, collinearity, and chromosomal position. According to the evolutionary tree, 190 LchiMYBs were divided into three main branches. LchiMYBs were evenly distributed across 19 chromosomes, with their collinearity, suggesting that segment duplication events may have contributed to LchiMYB gene expansion. Transcriptomes from eight tissues, 11 stages of somatic embryogenesis, and leaves after cold, heat, and drought stress were used to analyze the function of the MYB gene family. The results of tissue expression analysis showed that most LchiMYB genes regulated bark, leaf, bud, sepal, stigma, and stamen development, as well as the four important stages (ES3, ES4, ES9, and PL) of somatic embryogenesis. More than 60 LchiMYBs responded to heat, cold, and drought stress; some of which underwent gene duplication during evolution. LchiMYB3 was highly expressed under all three forms of stress, while LchiMYB121 was strongly induced by both cold and heat stress. Eight genes with different expression patterns were selected and verified by quantitative real-time PCR (qRT-PCR) experiments. The results suggested that these LchiMYBs may regulate Lchi growth development and resistance to abiotic stress. This study shows the cross-regulatory function of LchiMYBs in the growth and development, asexual reproduction, and abiotic resistance of Lchi. This information will prove pivotal to directing further studies on the biological function of Lchi MYBTFs in genetic improvement and abiotic stress response.